SITUATIONAL TESTS IN TENNIS FOR PLAYERS IN U-12 AGE CATEGORY (10-12 YEAR OLDS) - Vlatko Separović; Edin Užičanin; Mirza Mulahasanović (Sport Scientific And Practical Aspects, 2025)
Top-quality results in sports today can only be achieved by athletes who are selected at the right age, who are very talented and well prepared. Diagnostic procedures in sports are carried out with the goal of determining initial state of an athlete, evaluation of accomplished effects in certain stages of training process in sports and planning and organizing further stages of training process. This age category of tennis players (10-12 years old) marks the basic stage of training process, with the goal for tennis players to fully master technique of basic shots, and by that way to be in a position to have tennis fundamentals for the start of specialized tennis practice and to have a good foundation to continue their tennis development. Influenced by opinion that for this age the basic goal is that players master technique of basic shots, we defined a solution for designing measuring instruments through experimental work with two tennis players who are among the top 4 on the state ranking list for their age category. Suggested tests are: Test forehand 12, Test backhand 12, Test forehand – backhand 12, Test service 12. Presented tests for evaluating the acquisition of elements related to basic shot technique in tennis to eventual designing should go through stages of data collecting on larger sample of tested athletes. After data processing, it is possible to determine metrical characteristics of the tests.